Determination of an Optimal Revolving Credit Agreement - Berger, Paul D.; Harper, William K. (Journal of Financial and Quantitative Analysis, 1973)
Most large companies develop formal or informal agreements with banks to cover anticipated seasonal or temporary cash needs and/or to provide assurance of the availability of funds against unanticipated cash requirements. We address the problem of determining the optimal limits of available funds a company should maintain under a revolving credit agreement. Typically a company will negotiate a legal commitment with a bank or group of banks for a specified period of time, usually one to three years, in which the bank agrees to extend credit up to a specified maximum amount. During the duration of the commitment, the bank must lend money to the company whenever the company wishes to borrow, provided the amount of money borrowed does not exceed the maximum amount noted in the agreement. The company must not be in default of any of the restrictive covenants of the agreement, such as working capital limits, compensating balances, limits on other indebtedness, etc. Although the agreement itself provides for intermediate-term financing, the agreement often takes the form of short-term (30-60-90 days) renewable notes.